ANALISIS EFEKTIVITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DI SD ALAZHAR SYIFABUDI BOGOR TAHUN AJARAN 2021/2022 - FAUJIYAH, RESTI (Jurnal Gentala Pendidikan Dasar, 2022)
This research intended to find out the effectiveness of online learning during the pandemic at Al-Azhar Syifabudi Bogor Elementary School in 2021/2022. The sample in this study was a 6th grader of Al-Azhar Syifabudi Elementary School Bogor. This research is qualitative research with class action methods conducted online on Mathematics subjects. The study was conducted from the 2nd of August to the 2nd of October 2021. The results showed that online learning at Al Azhar Syifabudi Elementary School Bogor runs effectively because all teachers and students have facilities such as computers and smartphones connected to the internet. Evidenced by the learning results of students in cycle 1 that achieve the completion of minimum criteria as much as 80% and in cycle 2 as much as 100%. As well as the presentation of student attendance and liveliness in cycle 1 as much as 90% and in cycle 2 as much as 95%.